1986
DOI: 10.1139/v86-008
|View full text |Cite
|
Sign up to set email alerts
|

Ion exchange reactions of n-butylamine intercalates of tin(IV) hydrogen phosphate and hydrogen uranyl phosphate with cobalt(III) complexes

Abstract: The ion exchange reactions of n-butylamine intercalates of tin(IV) hydrogen phosphate and hydrogen uranyl phosphate towards carbonatotetraamminecobalt(III), chloropentaamminecobalt(III), and hexaamminecobalt(III) have been investigated. Independent of the complex cation charges, the amounts of Co(III) complex exchanged by the n-butylamine intercalate of tin(IV) hydrogen phosphate are practically the same. With the n-butylamine intercalate of hydrogen uranyl phosphate, the ionic exchange was completed and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In addition, certain uranyl compounds such as hydrogen uranyl phosphate (HUP) [40][41][42][43] and Cs 4 [(UO 2 ) 2 (V 2 O 7 )O 2 ] [44] have been shown to exhibit high cationic conductivities. In order to evaluate the potential for ion-exchange reactions of alkali metal cations with 1, samples were equilibrated with 0.01 M solutions of NaCl/NaOH, KCl/KOH, or CsCl/CsOH.…”
Section: Ion-exchange Studiesmentioning
confidence: 99%
“…In addition, certain uranyl compounds such as hydrogen uranyl phosphate (HUP) [40][41][42][43] and Cs 4 [(UO 2 ) 2 (V 2 O 7 )O 2 ] [44] have been shown to exhibit high cationic conductivities. In order to evaluate the potential for ion-exchange reactions of alkali metal cations with 1, samples were equilibrated with 0.01 M solutions of NaCl/NaOH, KCl/KOH, or CsCl/CsOH.…”
Section: Ion-exchange Studiesmentioning
confidence: 99%
“…Based on these new structures, the topological relations can be discerned [5] and used as a basis for materials design yielding solids with specific properties: e.g. selective ion-exchange [6][7][8][9][10][11][12], mixed-valency [13,14], ionic conductivity [15][16][17][18][19][20], enhanced fluorescence [21][22][23], magnetic ordering [11,24], non-linear optical properties [12,25], and differential gas absorption [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Clearfield and co-workers have demonstrated that in the synthesis of uranyl phosphonates, the presence of sterically demanding organic groups on the phosphonate ligands leads to the formation of novel structure types, including porous structures. Second, these materials may be envisioned to exhibit useful catalytic, ion-exchange, and intercalation properties. For example, hydrogen uranyl phosphate (HUP) is a fast hydrogen ion conductor and a versatile ion-exchange reagent, and Hutchings et al recently demonstrated that uranium oxide-based materials are effective oxidation catalysts for the destruction of a range of hydrocarbon- and chlorine-containing industrial pollutants . Finally, the existence of a number of stable oxidation states of actinides, such as uranium, offers the possibility of synthesising materials with useful optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%